The Effect of Financing Constraints on Corporate Investment: The SA-Index Approach - Novi ANRI; Zuliani DALIMUNTHE; Wasilah WASILAH (Communications of International Proceedings, 2021)
This study aims to analyze how the company's internal funds and investment opportunities impact the company’s investment decisions conditional to the financing constraints experienced. We classify companies into three categories based on the SA-Index; low, neutral, and high-financing constraints. We analyze 278 non-financial companies listed on the Indonesia Stock Exchange during 2014-2018 using multiple regression methods. There is an indication that companies experiencing a financing constraint have a higher investment-cash flow sensitivity than companies with a low financing constraint. We found that internal funds and investment opportunities positively and significantly affect companies' investment with high financing constraints and companies with the neutral category. Meanwhile, we did not find a statistically significant relationship between independent variables - the internal fund and investment opportunity - and investment for companies with low financing constraints.
Keywords: Cash Flow; Company Investment; SA-Index; Investment-Cash Flow Sensitivity